Arab Development Symposium Second : Invigorating SMEs in the Arab World - Rouis, Mustapha; Limam, Imed (World Bank, Washington, DC, 2014)
In March 2010, the Arab fund for economic and social development and the World Bank (Middle East and North Africa region) agreed to hold joint high-level development seminars around issues pertaining to the Arab World. These will be held on a regular basis, every 18 months or so, at the Arab fund premises in Kuwait. This note analyzes micro, small, and medium-scale enterprises (MSMEs) in the Arab World. A regional approach to promoting SMEs will have the added benefit of enhancing regional integration among MENA countries - a region which is one of the least integrated in the world. Finally, micro enterprises have an important development role as they stimulate economic inclusion, particularly among women and youth. The main recommendations are divided into two areas: policies and institutions.